Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00391-014-0647-4
|View full text |Cite|
|
Sign up to set email alerts
|

Design of pharmaceutical products to meet future patient needs requires modification of current development paradigms and business models

Abstract: Drugs represent the most common intervention strategy for managing acute and chronic medical conditions. In light of demographic change and the increasing age of patients, the classic model of drug research and development by the pharmaceutical industry and drug prescription by physicians is reaching its limits. Different stakeholders, e.g. industry, regulatory authorities, health insurance systems, physicians etc., have at least partially differing interests regarding the process of healthcare provision. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In particular, there is a growing number of drug products that are marketed with claims of being more age appropriate for older adults even though neither scientific methodology nor scientific data could be identified that would support such claims (Messina et al, 2015). This challenge need to be addressed already during the pharmaceutical development phase and need to be considered during drug product prescribing (Stegemann et al, 2014). The objective of this publication is to review important specific clinical and therapeutic characteristics of older adult patients and challenges to be considered during drug product development.…”
Section: Introductionmentioning
confidence: 93%
“…In particular, there is a growing number of drug products that are marketed with claims of being more age appropriate for older adults even though neither scientific methodology nor scientific data could be identified that would support such claims (Messina et al, 2015). This challenge need to be addressed already during the pharmaceutical development phase and need to be considered during drug product prescribing (Stegemann et al, 2014). The objective of this publication is to review important specific clinical and therapeutic characteristics of older adult patients and challenges to be considered during drug product development.…”
Section: Introductionmentioning
confidence: 93%
“…The studies were mostly from Europe (23) and North America (U.S. and Canada) (11) probably because they are the world's two main hubs of medicine production. 27 In Europe, the majority of papers were from the United Kingdom (6) and Germany (5). Nine studies came from the United States, and two were from Canada.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…The location, as reported by the authors, also seemed relevant. Single and multiple locations were identified, with the recurrent places being domiciles (14), hospitals, healthcare facilities or sheltered accommodations (13), ambulatory care (9) and community pharmacies (5). Only two studies were found involving a number of patients exceeding 1000 subjects.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased global longevity necessitates a re‐evaluation of the way societies are organised to adapt to the social, economic, environmental and healthcare consequences of the associated demographic shift 1–3 . Where an optimal strategy in the provision of healthcare services would be characterised by a holistic vision and multi‐, inter‐ and transdisciplinary work between, for example, medical and pharmaceutical care, drug development, accessibility, human factors, housing or social security, such a strategy cannot mature without domain‐specific understanding of expected challenges, potential solutions and useful interim measures 4,5 …”
Section: Introductionmentioning
confidence: 99%